A Flexible Wearable Multisensing Patch Integrating SWCNT-PtNPs Nanocomposites for Non-Invasive Clinical Biomarkers Monitoring in Sweat - Lucian-Gabriel Zamfir; Petru Epure; Ioana Cătălina Gîfu; Iuliana Răut; Mariana Constantin; Cristina Firincă; Nicoleta-Olguța Corneli; Mihaela Doni; Ana-Maria Gurban (Polymers, 2026)
The integration of enzyme-loaded polymeric matrices with carbon-based nanomaterials and metallic nanoparticles into wearable multisensing patches, coupled with miniaturized portable detection devices, enables real-time, highly sensitive, and simultaneous monitoring of key clinical biomarkers (e.g., glucose, lactate, and H2O2) in clinical and point-of-care applications. Multiplex biosensors were fabricated by modifying screen-printed carbon paste electrodes (SPEs) with different composite nanomaterials based on carbon nanomaterials such as multi-walled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), or fullerenol (FL), the redox mediator Prussian Blue, and platinum nanoparticles (PtNPs). Chitosan and sol–gel polymer matrices were used to immobilize the enzymes glucose oxidase (GOx) and lactate oxidase (LOx), thus ensuring not only increased sensitivity and operational stability, but also high specificity for biomarker detection (glucose and lactate). Among the nanomaterials used for the development of multiplex biosensors, the SWCNT-PtNP composite was highlighted by electrochemical studies as having a significantly superior electrocatalytic activity toward the reduction of H2O2. This reaction occurs at a low applied potential of only −0.2 V vs. Ag/AgCl, achieving a specific sensitivity of 224.6 mA·M−1·cm−2, over a concentration range of 0.07 to 28.26 mM, and a detection limit of 3.2 μM. When functionalized with enzymes, SWCNT-PtNP-based biosensors exhibit improved conductivity, allowing the detection of glucose and lactate at a potential of −0.05 V vs. Ag/AgCl. The specific sensitivities obtained are 20.25 mA·M−1·cm−2 for glucose and 94.76 mA·M−1·cm−2 for lactate, and the corresponding detection limits are 23.6 μM and 5.0 μM, respectively. Finally, a wearable patch integrating the multiplex (bio)sensor with a portable potentiostat enabled simultaneous, sensitive, and selective detection of glucose, lactate, and H2O2 in sweat samples.